The Effectiveness of Interactive Video Education Compared to Cadre Approach on Postpartum Mothers' Behavior in Umbilical Cord Care - Yuyun Yuniarti; Bima Suryantara; Gunarmi Gunarmi (Indonesian Journal of Global Health Research, 2025)
Umbilical cord infection significantly contributes to neonatal morbidity and mortality in border areas, with risky traditional care practices still commonly performed in Sanggau Regency. Objective: This study aimed to compare the effectiveness of interactive video education with health cadre approach in improving umbilical cord care behavior. The research design used an open-label randomized controlled trial with subjects of third-trimester pregnant women with gestational age more than thirty-seven weeks. Samples were taken using total sampling with forty-three initial respondents, then dropout occurred resulting in forty-two respondents divided into video group twenty-one people and cadre group twenty-two people. Before randomization, stratification was performed based on education and parity using simple random sampling with Excel RAND function. The video group received education through validated interactive videos, while the cadre group received lectures and demonstrations. Assessment was conducted on knowledge, attitudes, and practices using valid and reliable structured instruments from postpartum until umbilical cord separation. Data were analyzed using Mann-Whitney U, chi-square, and multiple logistic regression. Interactive video was significantly more effective in improving knowledge with odds ratio thirteen point six times greater, but no significant difference for attitudes and practices. Multivariate analysis showed education variables had significant effect with prediction accuracy of eighty-one percent. No single method was superior for all behavioral aspects, so combining both methods could be an optimal strategy to comprehensively improve umbilical cord care behavior Interactive video was more effective in improving knowledge, while the cadre-based approach had a stronger influence on shaping attitudes and practices, although the results were not statistically significant.